Sosial Ekonomi dan Pengetahuan Ibu Terhadap Pemberian Asi Eksklusif - Nurfatimah Nurfatimah; Pertiwi Labusa; Fransisca Noya; Lisda Widianti Longgupa; Christina Entoh; Nilda Yulita Siregar; Kadar Ramadhan; Hastuti Usman (Poltekkes Kemenkes Padang, 2022)
The coverage of exclusive breastfeeding at Puskesmas Tokorondo from 2018-2019 decreased from 50.8% to 28%. Lack of knowledge and intensive promotion of formula milk is one of the causes to low exclusive breastfeeding. The aim of this study was to discover the relationship between socio-economic factors and the level of knowledge of mothers about exclusive breastfeeding at the Puskesmas Tokorondo. This study using an analytical method with a cross-sectional approach. The number of population were 46 people that is mothers who have toddlers aged 6-12 months in the working area of Puskesmas Tokorondo. The sample in this study was 36 people, using consecutive sampling technique. Research shows that more exclusive breastfeeding is found on the low-educated mothers (60%), unemployed mothers (23.5%), high-income (50%), and well-informed (100%). There is a correlation between the knowledge level and exclusive breast-feeding (p= 0.001) while education (p= 0.217), work (p=1,000), and income (p= 0.436) has no relation to exclusive breast-feeding. It is hoped that health workers can be a source of information to the importance of exclusive breastfeeding for infant aged up to 6 months and after 6 months old. After six months, continued with the complementary feeding as well as continuing the breastfeed until the aged of 2 years, along with the support of the husband and particularly the family as an effort to increase the scope of exclusive breastfeeding.